(untitled) (Journal of the College of Education for Women, 2026)
Imam Muhammad ibn Isma’il ibn Ja’far al-Sadiq (peace be upon him) represents a controversial figure in the history of Islamic sects, as various groups claimed affiliation with him, particularly those who embraced Isma’ilism as a theological belief and way of life. His public and secretive life sparked disagreements in narrating his accounts, with historical sources differing on the locations of his travels, the variety of his titles, as well as the time, place, and location of his death and burial. Some even claimed that he went into a prolonged occultation and is still alive today. He was given many titles, including al-Maktum (the Concealed), a title recognized in the Imami, theological, historical, and Isma’ili traditions. He is considered one of the "concealed" imams in Isma’ilism. His life took on various phases, each surpassing the previous in complexity, a characteristic that influenced the Isma’ilis due to the sanctity of his personality.